Analysis of Financial Fraud and Governance in Guangyuyuan - Liu, Mengmeng (Asia Pacific Economic and Management Review, 2025)
In recent years, with the rapid development of the capital market, cases of financial fraud by listed companies have gradually increased, leading to increasingly severe economic consequences. This study takes Guangyuyuan Chinese Medicine Co., Ltd. as the research subject, thoroughly analyzing its methods and motivations for financial fraud, and derives corresponding preventive measures based on this case. The aim of this research is to provide references and insights for the prevention and governance of financial fraud in listed companies.